2018
DOI: 10.1038/s41598-018-36172-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of macro- and microplastics on an agricultural farmland

Abstract: Microplastic contamination of aquatic ecosystems is a high priority research topic, whereas the issue on terrestrial ecosystems has been widely neglected. At the same time, terrestrial ecosystems under human influence, such as agroecosystems, are likely to be contaminated by plastic debris. However, the extent of this contamination has not been determined at present. Via Fourier transform infrared (FTIR) analysis, we quantified for the first time the macro- and microplastic contamination on an agricultural far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
247
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(293 citation statements)
references
References 39 publications
10
247
4
1
Order By: Relevance
“…This non-target plastic mixture consisted of 19 % PET from recycled bottles (PETKA CZ, Brno, Czech Republic), 11 % poly(methyl methacrylate) (PMMA) ground from a commercial plexiglass (Bundesanstalt für Materialforschung und -prüfung, Berlin, Germany), 41 % polyvinyl chloride (PVC) (Aldrich Chemistry, Taufkirchen, Germany), and 29 % tire wear particles (TWP) from a test rig at Bundesanstalt für Straßenwesen, Bergisch Gladbach, Germany. Content and composition of the non-target polymers were based on findings by Piehl et al (2018) to reflect realistic conditions in agricultural soil.…”
Section: Extraction Of Plastic Debris From Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…This non-target plastic mixture consisted of 19 % PET from recycled bottles (PETKA CZ, Brno, Czech Republic), 11 % poly(methyl methacrylate) (PMMA) ground from a commercial plexiglass (Bundesanstalt für Materialforschung und -prüfung, Berlin, Germany), 41 % polyvinyl chloride (PVC) (Aldrich Chemistry, Taufkirchen, Germany), and 29 % tire wear particles (TWP) from a test rig at Bundesanstalt für Straßenwesen, Bergisch Gladbach, Germany. Content and composition of the non-target polymers were based on findings by Piehl et al (2018) to reflect realistic conditions in agricultural soil.…”
Section: Extraction Of Plastic Debris From Soilmentioning
confidence: 99%
“…However, plastic concentrations were estimated from particle sizes and densities without stating limits of detection (LODs) or limits of quantification (LOQs). Similarly, Piehl et al (2018) screened agricultural soil for plastic debris and found 0.3 ± 0.4 particles ha −1 , but neglected all particles smaller than 1 mm due to the challenging sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Around 110,000 to 730,000 tons of MPs are annually transferred to agricultural soils in Europe and North America, which is more than the total burden of MPs currently in our oceans [8][9][10]. In a study on macro-and microplastics in agricultural soil, up to 205 macroplastic pieces per hectare (ha) and 0.34 ± 0.36 MPs pieces per kilogram soil (dry weight) were detected; illustrating the vast extent of soil contamination [11]. Entry routes of MPs into terrestrial systems are not well known; however, initial studies have attempted to elucidate these possible pathways, such as, for example, via the use of organic fertilizers as a vehicle for MP entry [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…They originate from many sources (Bläsing & Amelung, ) and are almost certainly ubiquitous around the globe, being carried by wind to even the remotest places (Allen et al, ). However, urban (Fuller & Gautam, ), riparian (Scheurer & Bigalke, ) and agricultural soils (Corradini et al, ; Liu et al, ; Piehl et al, ; Zhang & Liu, ) have so far received the bulk of research focus (Figure c). Soils are the basis of virtually all terrestrial ecosystems and one of human society's most important natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…Diagram showing common microplastic shapes, six of the most common plastic polymers (Geyer, Jambeck, & Law, ), and sources and observed concentrations of microplastics in urban (1: Fuller and Gautam ()), riparian (2: Scheurer and Bigalke ()) and agricultural soils (3: Zhang and Liu (), 4: Piehl et al (), 5: Corradini et al ()). Note that microplastic concentration in (5) is given in particles per g, not particles per kg…”
Section: Introductionmentioning
confidence: 99%